The perception of emotions in L1 and L2 among Arabic-English bilinguals: A qualitative investigation - Almadanat, Dina; Kholoud Almadanat (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2024)
Emotions in the context of bilingualism present a complex and dynamic field of study (Dewaele, 2014). The current research examines the emotional experiences of ten Jordanian international Ph.D. students in Hungary, who are proficient in English as their second language (L2). Participants, contacted through social media, represent a diverse group of both genders, aged between 25 and 28. The study follows a qualitative research design. Semi-structured interviews were conducted to delve into the participants' emotional perceptions and expressions. By conducting open-ended interviews, the research aims to gain profound insights into how bilingual individuals experience and articulate emotions in their daily lives. The findings contribute to the broader exploration of the emotional dynamics experienced by bilingual individuals, highlighting the significance of personal and cultural factors in shaping emotional experiences. This research holds relevance not only for academics and researchers in the field of bilingualism but also for educators, counselors, and policymakers, as it provides a deeper understanding of the emotional aspects of language use in multicultural and multilingual contexts. Additionally, the study adds a valuable perspective to the existing body of knowledge on bilingualism and emotions, ultimately enriching our comprehension of this intricate phenomenon.